Valuma-alueen vaikutus pienten arktisten järvien limnologiaan ja orgaanisen aineksen kulkeutumiseen - Galkin, Annukka (Helsingfors universitet, 2015)
The arctic region is sensitive to climate change impacts. Arctic lakes are typically transparent and shallow. Environmental changes occurring in the catchment reflect to DOC (dissolved organic carbon) and nutrients concentration of arctic lakes. Furthermore, productivity of lakes, organic matter transport and mineralization will change. This thesis examines how the catchment characteristics currently impact the limnology of arctic lakes and assess future changes when temperature and precipitation will increase. Special attention is given to DOC due to its strong impact on the lake ecosystem. Water and sediment samples were collected from 31 lakes from Ivalo to Utsjoki (68°47' and 69°55') at the end of July 2014. pH was measured in situ and the vegetation type of catchment was observed. LOI 550- % (loss-on-ignition) and chlorophyll-a-sediment were measured from surface sediment (0-2 cm). DOC, TP (total phosphorus), TN (total nitrogen), chl-a-water (chlorophyll-a-water), CDOM (colored dissolved organic carbon) components C1-C4,C6, SUVA (specific UV-absorbance), FI-index (fluorescence index) and HI-index (humification index) were measured from water samples from the epilimnion. Catchment variables were analyzed by using GIS (geographical information system) to determine boundaries, area, topography and altitude of catchments. Based on general map raster of National land survey of Finland © wetland- %, forest- %, tundra- % and lake- % were digitized. Vegetation type was determined based on general map raster and field observations. The July mean temperature during 1984–2013 was calculated based on mean temperature raster of Finnish meteorological institute ©. Principal component analysis (PCA) was used to determine catchment variables which most impact the limnology. Based on principal component analysis results the most effective catchment variable is wetland -% which has a strong impact on DOC, nutrients, chlorophyll-a-water, CDOM components C1-C4, C6 and HI-index. Wetlands are important source of DOC and ...